THE THEORETICAL ASPECTS OF REALISATION OF THE HISTORICISM PRINCIPLE IN THE LESSONS OF STYLISTICS OF THE UKRAINIAN LANGUAGE IN HIGH SCHOOL - Popovych, Anzhelika S. (Educological discourse, 2017)
The article deals with the analysis of the theoretical aspects the historicism principle usage during the study of Stylistics of the Ukrainian language by future Ukrainian language and literature teachers. The methodological, moral, valuable and culturological approaches of linguodidacts to the historicism principle usage are outlined. Due to the peculiarities of the organisation of educational process in higher educational institutions, the attention is paid to studying (theoretical, educational and practical), scientific and educational levels of studying of the historical aspects of the Stylistics of the Ukrainian language. It is stated that the principle of historicism is realised by means of basic, additional, self-educational and integrated models. The main model - the issues of historical aspects of Stylistics are the components of the curriculum of discipline, complement the main information and are studied in the lessons in higher educational establishments. In the additional model the questions of the history of Stylistics are the components of selective academic disciplines, certain selective disciplines are studied at meetings of a students' scientific circle or a problem group. The self-educational model involves studying the questions of the history of Stylistics during independent work of a student. The integrated model is built up by means of the combination of other models. A high level of knowledge in the history of Stylistics of the Ukrainian language is possible by means of the use of a conglomerate of auditorial and unsupervised work, as well as taking into account the interest of higher education graduates by means of the reading of selective academic disciplines. The genesis of Stylistics of the Ukrainian language, functional styles, cultural-historical aspects of texts and their historical-stylistic analysis should be the objects of scientific and historical research in Stylistics. It is concluded that the insufficient use of the historical principle in the study of Stylistics of the Ukrainian language, the rejection of the complete study reduces the potential of this science greatly. It is impossible to comprehend the Stylistic areas and comprehend them comprehensively without appealing to the historical explanation of modern stylistic phenomena and concepts.